TINJAUAN HUKUM KEAMANAN SIBER DALAM MENGHADAPI EKONOMI DIGITAL PADA ERA KONTEMPORER - Nabila Alif Radika Shandy; Abhinaya Wahyu Satrio (Universitas Borneo Tarakan, 2023)
AbstractTechnology is one of many important factors in economic activities. Many sectors in Indonesia that are growing up lately. Meanwhile, technology always comes together with the internet. the information and communications technology development recently is like a double-edged sword, which brings a positive impact to humanity for digital economy purposes or for negative purposes like cyber crime. Cybercrime in Indonesia frequently happens like breaches on personal or group of people's data. Many cases of breached data in Indonesia in 2020 until 2022 are increasing. These cases not only strike the government sector, but also on the e-commerce sector. This research contains one research question, how is the implementation of cyber security law in dealing with the digital economy in the contemporary era? The research method used in this research is juridical-normative using primary, secondary and tertiary legal materials. Then, using the legislation and case approach. This research gives results, which is the law's role on cyber security in dealing with digital economy recently is not yet at maximum level, because PDP's law still contains deficiencies, then in order to face digital economy, the next step is to pass the bill of security and cyber resilience to become a law.Key word: Cyber security, Digital Economy, Contemporary Era.